2020
DOI: 10.1007/s10461-020-03068-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among HIV Healthcare Providers During the COVID-19 Pandemic in China: Mediating Roles of Institutional Support and Resilience

Abstract: Psychological distress among healthcare providers is concerning during COVID-19 pandemic due to extreme stress at healthcare facilities, including HIV clinics in China. The socioecological model suggests that psychological distress could be influenced by multi-level factors. However, limited COVID-19 research examined the mechanisms of psychological distress among HIV healthcare providers. This study examined organizational and intrapersonal factors contributing to psychological health during COVID-19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 57 publications
(68 reference statements)
4
38
0
Order By: Relevance
“…Four studies reported a strong link between personal resilience and depression (Luceno-Moreno et al ., 2020; Lin et al ., 2020; Khalaf et al ., 2020; Yoruk & Guler, 2020), suggesting that interventions to enhance resilience among healthcare workers may help prevent or reduce the occurrence of depression in this population during the COVID-19 pandemic. In addition to depression and anxiety, a few more studies confirmed the protective role of psychological resilience against psychological stress (Tam et al ., 2020; Luceno-Moreno et al ., 2020; Khalaf et al ., 2020), emotional exhaustion (Di Monte et al ., 2020), and PTSD symptoms (Maiorano et al ., 2020; Lucero-Moreno et al ., 2020; Li et al ., 2020). In one study, resilience partially mediated the association between institutional support and coronavirus-related distress (Tam et al ., 2020).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Four studies reported a strong link between personal resilience and depression (Luceno-Moreno et al ., 2020; Lin et al ., 2020; Khalaf et al ., 2020; Yoruk & Guler, 2020), suggesting that interventions to enhance resilience among healthcare workers may help prevent or reduce the occurrence of depression in this population during the COVID-19 pandemic. In addition to depression and anxiety, a few more studies confirmed the protective role of psychological resilience against psychological stress (Tam et al ., 2020; Luceno-Moreno et al ., 2020; Khalaf et al ., 2020), emotional exhaustion (Di Monte et al ., 2020), and PTSD symptoms (Maiorano et al ., 2020; Lucero-Moreno et al ., 2020; Li et al ., 2020). In one study, resilience partially mediated the association between institutional support and coronavirus-related distress (Tam et al ., 2020).…”
Section: Methodsmentioning
confidence: 93%
“…A number of papers examined the effects of psychological resilience on the mental health of healthcare workers (12/31) (Di Monte et al ., 2020; Huang et al ., 2020a; Khalaf et al ., 2020; Labrague & De los Santos, 2020a; Labrague & De los Santos, 2020b; Li et al ., 2020; Lin et al ., 2020; Lucero-Moreno et al ., 2020; Maiorano et al ., 2020; Mohave et al ., 2020; Tam et al ., 2020; Yoruk & Guler, 2020). Of these, eight studies reported a protective role of psychological resilience against coronavirus-related anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Parental psychological distress was assessed using the Patient Health Questionnaire (PHQ-4), with four items asking mood disorder symptoms, including two items for depression and other two items for anxiety ( Löwe et al, 2010 ). The PHQ-4 has been applied in Chinese population previously, suggesting good validity and reliability ( Tam et al, 2021 ; Zhang et al, 2020 ). It assessed the frequency of the following symptoms that participants experienced in the past two weeks (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The survey, about 15 min in response time, assessed participants' perceived challenges for delivering HIV care service and observed patient HIV care outcomes during the COVID-19 outbreak (January to March 2020). We employed SO JUMP system technology, a widely used Chinese online survey tool similar to Amazon Mechanical Turk in data collection (Tam et al, 2020). The eligibility criteria for participants included: (1) currently providing HIV-related care and services; (2) 18 years of age or older;…”
Section: Participants and Proceduresmentioning
confidence: 99%